Pengaruh Persepsi Mahasiswa Tentang Investasi Terhadap Minat Investasi Saham di Pasar Modal Syariah (Studi pada Mahasiswa Angkatan 2020 Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Rustam Rustam; Junaidi Junaidi; Hariri Hariri (Universitas Islam Malang, 2023)
Investment is a business activity that contains risk because there is an element of uncertainty. In the view of Islam, investment is one of the knowledge that has an important role in the economy. By investing the assets we have, we become productive and also bring benefits to others. The capital market also has an important role in economic activity, the development of the capital market is one source of economic progress, and the development of the capital market is one of the sources of economic progress. In Indonesia, which is included in the category of developing countries, the capital market is one of the alternatives in development so that it gives birth to various kinds of thoughts or perceptions of students that will encourage interest in investment or vice versa.Keywords: Student perception, investment interest